2023
DOI: 10.3390/ma16134551
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Production during Bio-Waste Composting under Different Temperature and Aeration Regimes

Abstract: Despite the development of biorefinery processes, the possibility of coupling the “conventional” composting process with the production of biochemicals is not taken into account. However, net carbon monoxide (CO) production has been observed during bio-waste composting. So far, O2 concentration and temperature have been identified as the main variables influencing CO formation. This study aimed to investigate CO net production during bio-waste composting under controlled laboratory conditions by varying aerati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…It was observed that emissions of CO increased with time and temperature (Supplementary Materials Figure S2), which was previously indicated with our own study [61]. This is an effect of the thermochemical reactions and biological activities of microorganism.…”
Section: Co Emissionssupporting
confidence: 84%
“…It was observed that emissions of CO increased with time and temperature (Supplementary Materials Figure S2), which was previously indicated with our own study [61]. This is an effect of the thermochemical reactions and biological activities of microorganism.…”
Section: Co Emissionssupporting
confidence: 84%
“…On this basis, the heating box with the vent of the composting equipment is designed as a rectangle, and the size of the heating box refers to the structure of the fermentation tank. This paper describes the design of a heating box made of 304 stainless steel, with dimensions of 500 mm × 350 mm × 300 mm and vents [41]. The box consists of a top cover and a main structure, with an electric heating pipe installed in the middle of the top cover.…”
Section: Installation Position For Low and Medium-voltage Application...mentioning
confidence: 99%
“…Animal manure is both a rich source of organic matter and a potential environmental pollutant, containing pathogenic bacteria and nutrients which can contribute to water eutrophication and soil contamination if improperly treated [8,9]. Recognizing these challenges, China has outlined goals for agricultural sustainability to ensure the comprehensive utilization of livestock waste and crop straw by 2030 [9][10][11]. Given the urgency of harmless manure treatment, composting-a widely used method-transforms livestock and poultry manure into organic fertilizer, increasing agricultural yield and mitigating soil degradation from traditional fertilizers [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%